Comparative Study of the Mangrove Ecosystems of Douala-Edea Reserve (Cameroon) and Songor Ramsar Site (Ghana) Using Parameters of Ecological Value - Ntyam, S.C.O. (University of Ghana, 2014)
In most tropical countries including Ghana and Cameroon, knowledge of ecological importance of mangrove ecosystem in terms of litter production, structural characteristics, water and soil properties, has been qualitatively well documented and recognised. However, there is scanty quantitative scientific data to back this up. The purpose of this research dissertation was to study and compare the mangrove ecosystems of Cameroon and Ghana two contrasting coastal zones, using parameters of ecological value and to have a better understanding of their interrelationships within mangrove ecosystem as well as the impact of their values or roles to the global ecosystem (marine and coastal) within the West and Central African ecoregion. The study was conducted within the period of two years for both countries (One year in each country), Two major sites were chosen in Ghana (Songor Ramsar site) and Cameroon (Douala Edea Reserve). In each site, three mangrove stands: 1) Avicennia, 2) Rhizophora and mixed (Rhizophora and Avicennia) were selected and marked out, and parameters like litterfall, structural characteristics, water and soil properties were assessed. This research on mangrove ecosystem addressed four objectives: (1) assessment of the structural parameters; (2) assessmentof litter production; (3) determination of physicochemical and climatic factors affecting mangrove structure and productivity; (4) Show the interrelationships between mangrove resources in both countries. The results in both countries showed that, (1) Leaves, twigs, flowers and fruits were present in litter samples all over the study period with highest peak mainly in the dry season, and leaf production accounted for more than 80% in each country; (2) High values of most of the major nutrients (N, P, K, Mg, Ca) investigated and used in evaluation of mangrove ecosystem importance were recorded between March and October for Cameroon mangroves and in December for Ghana mangroves. (3) The mean highest species density was observed in Rhizophora for Cameroon and Avicennia and mixed in Ghana. The mangrove of Cameroon showed greater heights than their Ghanaian counterparts. (4) The values of Physical parameters (DO, BOD, EC, TDS, TSS), and nutrients were most often high in Cameroon, compared to Ghana. Mangrove waters were also found more alkaline in Cameroon than in Ghana. (5) It was observed that in both countries, Avicennia had the highest percentage of silt. In addition to that nitrogen ,phosphorus, leaves (Litterfall), nitrate, Biochemical Oxygen Demand, pH, Phosphate, salinity, Conductivity (Mangrove Water ), percentage organic nitrogen, electrical conductivity, acidity, Exchangeable magnesium, ECEC Effective Cation Exchange Capacity, and available phosphorus Av P (Mangrove Soil), height, basal area and density (Structural characteristics) were the major discriminatory ecological features of the mangroves of Ghana and Cameroon. Correlations with litterfall, structural, water and soil variables indicated that mangrove ecosystem within and across the countries respond differently to environmental conditions. The combination of rainfall, temperature and salinity was a good predictor of variability in the production of litterfall in both countries. This study contributes to a better understanding of how mangrove ecosystems function. Additional work in other geographic areas within the West and Central African ecoregion is needed to provide a broader perspective on the ecological importance of mangrove ecosystem and their impact on the nearby marine and coastal areas.
Thesis (PhD) - University of Ghana, 2014